Bactericidal Activity of an Imidazo[1, 2-a]pyridine Using a Mouse M. tuberculosis Infection Model - Cheng, Yong; Moraski, Garrett C.; Cramer, Jeffrey; Miller, Marvin J.; Schorey, Jeffrey S. (PLOS ONE, 2014)
Tuberculosis remains a global threat due in part to the long treatment regimen and the increased prevalence of drug resistant M. tuberculosis strains. Therefore, new drug regimens are urgently required to combat this deadly disease. We previously synthesized and evaluated a series of new anti-tuberculosis compounds which belong to the family of imidazo[1,2-a]pyridines. This family of compounds showed low nM MIC (minimal inhibitory concentration) values against M. tuberculosis in vitro. In this study, a derivative of imidazo[1,2-a]pyridines, (N-(4-(4-chlorophenoxy)benzyl)-2,7-dimethylimidazo[1,2-a]pyridine-3-carboxamide) (ND-09759), was selected as a promising lead compound to determine its protective efficacy using a mouse infection model. Pharmacokinetic analysis of ND-09759 determined that at a dosage of 30 mg/kg mouse body weight (PO) gave a maximum serum drug concentration (Cmax) of 2.9 µg/ml and a half-life of 20.1 h. M. tuberculosis burden in the lungs and spleens was significantly decreased in mice treated once daily 6 days per week for 4-weeks with ND-09759 compared to untreated mice and this antibiotic activity was equivalent to isoniazid (INH) and rifampicin (RMP), two first-line anti-TB drugs. We observed slightly higher efficacy when using a combination of ND-09759 with either INH or RMP. Finally, the histopathological analysis revealed that infected mice treated with ND-09759 had significantly reduced inflammation relative to untreated mice. In conclusion, our findings indicate ND-09759 might be a potent candidate for the treatment of active TB in combination with current standard anti-TB drugs.